CEO compensation and performance in US private foundations. (8th February 2018) - Allen, Arthur; McAllister, Brian
Abstract: In a large sample of US private foundations, we examine the association between CEO compensation and an accounting‐based measure of performance, administrative efficiency. We document a positive pay–performance association across time within foundations, but a negative association across foundations. We interpret our evidence as follows: some foundation boards reward CEOs for high administrative efficiency, which results in a positive pay–performance association. However, some foundations are poorly monitored relative than others, resulting in higher CEO compensation and lower efficiency.